2012
DOI: 10.1159/000335262
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Rotavirus Infection by Membrane-Impermeant Thiol/Disulfide Exchange Blockers and Antibodies against Protein Disulfide Isomerase

Abstract: Objectives: Determining the effect of membrane-impermeant thiol/disulfide exchange inhibitors on rhesus rotavirus infectivity in MA104 cells and investigating protein disulfide isomerase (PDI) as a potential target for these inhibitors. Methods: Cells were treated with DTNB [5,5-dithio-bis-(2-nitrobenzoic acid)], bacitracin or anti-PDI antibodies and then infected with virus. Triple-layered particles (TLPs) were also pretreated with inhibitors before inoculation. The effects of these inhibitors on α-sarcin co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 130 publications
0
40
0
2
Order By: Relevance
“…In addition, there is some previous knowledge about the implication of certain cellular molecules in the rotavirus infection process (Lopez & Arias 2006, Calderon et al 2012). To get insight into the mechanisms supporting the antiviral action of AA, IBF, DCF and NAC, their impact on the expression of COX-2, ERp57, Hsc70, NF-κB, Hsp70, PDI or PPARγ was evaluated using immunochemistry, indirect immunofluorescence, ELISA, WB and confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is some previous knowledge about the implication of certain cellular molecules in the rotavirus infection process (Lopez & Arias 2006, Calderon et al 2012). To get insight into the mechanisms supporting the antiviral action of AA, IBF, DCF and NAC, their impact on the expression of COX-2, ERp57, Hsc70, NF-κB, Hsp70, PDI or PPARγ was evaluated using immunochemistry, indirect immunofluorescence, ELISA, WB and confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…ECwt infection of villus cells induced the expression of host-encoded proteins COX-2, ERp57, Hsc70, NF-κB, Hsp70, PDI and PPARγ as detected in cross-sections from intestinal villi. It deserves to be mentioned that Hsc70 and PDI have been identified as rotavirus-interacting proteins during the infection of MA104 cells (Guerrero et al 2002, Calderon et al 2012), whereas COX-2 has been found to be required and induced by rotavirus infection of Caco-2 cells (Rossen et al 2004). On the other hand, the influenza virus-induced ER stress has been associated with increased levels of ER chaperone ERp57 (Roberson et al 2012), whilst recruitment of Hsp70 chaperones has been found to be an important component of viral survival strategies (Mayer 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in MA104 cells thiol blockers and PDI inhibitors decreased the entry of rotavirus, indicating the involvement of thiols for infectivity (Calderon et al, 2012). …”
Section: Pdi and Infectionmentioning
confidence: 99%
“…The inner layer is composed of the core shell (VP2), which encloses VP1, VP3 and the genomic RNA [4,5] . Rotavirus entry into the host cell seems to be mediated by the sequential interaction of virions with various cell surface molecules including sialic acid (SA) [6] , heat shock cognate protein 70 (Hsc70) [7,8] , integrins [9][10][11] and protein disulfide isomerase (PDI) [12] . Virion penetration into the host cell involves the loss of VP4 and VP7 converting the TLP into a double-layered particle (DLP), which becomes transcriptionally active by generating positive-strand RNAs (mRNAs) [13] .…”
Section: Introductionmentioning
confidence: 99%